Description of asymmetric hysteretic behavior based on the Bouc-Wen model and piecewise linear strength-degradation functions. (15th February 2019) - Kim, Sung-Yong; Lee, Cheol-Ho
Highlights: Reviewed the Bouc-Wen class models. Proposed the Bouc-Wen models with piecewise linear functions. Verified the proposed model on the basis of the cyclic test results exhibited highly asymmetric hysteresis. Abstract: The Bouc–Wen model is one of the widely employed models in engineering for the description of hysteretic behavior. One of the major challenges in applying this model is how to describe the asymmetric hysteresis behavior. This paper first reviews previous models ranging from the original Bouc-Wen model to its several generalized models that have evolved. From a phenomenological perspective, this study combined the Bouc-Wen models with piecewise linear functions that can capture the hysteretic behavior with asymmetric strength degradation. The proposed model was verified on the basis of the cyclic seismic test results of welded steel moment connections with composite floor slabs.